1991
DOI: 10.1139/t91-051
|View full text |Cite
|
Sign up to set email alerts
|

The Heather Hill landslide: an example of a large scale toppling failure in a natural slope

Abstract: This paper is an inquiry into the suspected relationship between toppling and large deep-seated landslides along the Beaver Valley, Glacier National Park, British Columbia. The study area includes the Heather Hill landslide, one of several in the valley, and adjacent slopes that show varying degrees of toppling disturbance. The development of the Heather Hill landslide is simulated using the distinct element method of numerical analysis. The rock mass is modelled using deformable columns whose boundaries repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The geometry of the jointed slope is resolved by first approximating the angle of the bases of the rock blocks subjected to the failure modes. Scholars [25][26][27] indicated that the toppling blocks tend to be stepped on the base planes and the approximation of the base plane angle is usually taken as the sum of the initial weak plane angle and the stepped angle which varies between 10° and 30°. Considering the weak plane angle during toppling failure, variations of stepped angles and the counter-tilted angle, the angle of the base planes ( ψb ) is estimated using Eq.…”
Section: Rock Slope Geometrymentioning
confidence: 99%
“…The geometry of the jointed slope is resolved by first approximating the angle of the bases of the rock blocks subjected to the failure modes. Scholars [25][26][27] indicated that the toppling blocks tend to be stepped on the base planes and the approximation of the base plane angle is usually taken as the sum of the initial weak plane angle and the stepped angle which varies between 10° and 30°. Considering the weak plane angle during toppling failure, variations of stepped angles and the counter-tilted angle, the angle of the base planes ( ψb ) is estimated using Eq.…”
Section: Rock Slope Geometrymentioning
confidence: 99%
“…With the loss of rock and soil mass from the outer surface of the slope, the inner part of the slope is gradually exposed to repeated weathering, which weakens the slope stability. Notably, weathered and washed loose deposits with a high degree of laterization may finally become the source materials for debris flows [48,49]. As shown in Table 1, mudstone, shale, silty mudstone, and other clay rocks on the slope of a soft-hard interbedded structure are easily scoured and soften in the presence of water.…”
Section: Weathering and Slope Scouringmentioning
confidence: 99%
“…Toppling is the phenomenon in which a hard rock mass topples to the free face about a certain point at the bottom in response to unloading and rebounding or when subjected to the actions of gravity and forces exerted by adjacent units or by fluids. If the dumping amplitude is adequately large, then it may collapse under the moment of gravity, and this might even lead to a deep sliding failure at the base [2,45,48].…”
Section: Topplingmentioning
confidence: 99%
“…The technique is particularly successful in the modelling of rock slopes in engineering geology which contain prominent discontinuity sets (Hsu and Nelson, 1990). Examples include the stability analysis of undermined cliffs in the Loire valley (Homand-Etienne et al, 1990), defining toppling mechanisms and controlling failure surfaces (Ishida et al, 1987;Pritchard and Savigny, 1991), the assessment of mining-induced subsidence in Australia (O'Connor and Dowding, 1990) and tunnel stability (Makurat et al, 1990). Importantly, UDEC can represent the discontinuous deformation of jointed rock and many recent studies have been used to verify the link between real-world problems and UDEC as an appropriate analytical solution (Brady et al, 1990;Choi and Coultard, 1990;Lemos, 1990;Senseny and Simons, 1994).…”
Section: The Modelling Approachmentioning
confidence: 99%